Rekonstruksi Keadilan Sebagai Praksis Profetik-Emansipatoris: Kritik Atas Defisit Normativitas Dan Agenda Transformasi Sosial Dalam Studi Islam Kontemporer - Kamelya Dinana; Siti Firdaini; Fanida Khoirun Nisa'; Ali Hasan Siswanto (Indo Publishing, 2026)
Justice in contemporary Islamic studies faces an epistemic paradox: it is normatively rich yet practically impoverished. The discourse of justice remains trapped in textual articulations al-‘adl, al-qisṭ, and al-iḥsān while failing to respond to the realities of structural inequality, legal bias, and increasingly complex social fragmentation. A research gap emerges from the weak integration between Qur’anic concepts of justice, modern theories of social transformation, and the absence of an operational model capable of linking prophetic values with concrete social intervention. Existing literature remains fragmented: Sufism is separated from public ethics, amar ma‘rūf nahi munkar is reduced to moral advice, and counseling is treated merely as an individual practice rather than an emancipatory mechanism. This article employs a prophetic-emancipatory theoretical approach that integrates the epistemology of tawḥīd, Sufi ethics, and critical justice theory to reconstruct justice as a transformational praxis. The study adopts a qualitative-critical methodology through hermeneutical and discourse analysis, enabling the exploration of the relationship between revealed values, social structures, and contemporary dynamics of injustice. The central argument of this article asserts that justice can function transformatively only when actualized through prophetic-emancipatory counseling, a model of social counseling that positions amar ma‘rūf nahi munkar as a mechanism for diagnosis, critique, accompaniment, and community empowerment. Scientifically, the article contributes by offering a new theoretical model of prophetic justice that is integrative connecting spirituality, ethics, and social praxis and by expanding the domain of counseling in Islamic studies from the individual level to a structural-emancipatory framework. These findings are expected to serve as a conceptual foundation for future research and social justice movements inspired by prophetic values.